Synthetic gene construct expressing a repeated and highly immunogenic epitope of the Plasmodium falciparum antigen Pf155. - Aslund, L (1987)
The Plasmodium falciparum-derived antigen Pf155 contains two blocks of tandemly repeated amino acid sequences. A pair of complementary oligonucleotides, encoding the C-terminally located repeat Val-Glu-His-Asp-Ala-Glu-Glu-Asn, were synthesized. The oligonucleotides were polymerized by ligation, and the resulting multimers were cloned into an expression vector. One construct that contained four copies of the repeat was expressed in Escherichia coli. The product, a fusion protein, was soluble and produced in high amounts. It reacted in immunoblotting with a monoclonal antibody to a synthetic octapeptide (Glu-Glu-Asn-Val-Glu-His-Asp-Ala). Rabbits immunized with partially purified fusion protein, either with or without adjuvant, formed antibodies against this octapeptide. These antibodies reacted with Pf155 both in parasite extracts and when deposited in the membrane of infected erythrocytes. Furthermore, these antibodies inhibited merozoite reinvasion in vitro as efficiently as human antibodies to the octapeptide sequence in Pf155, induced by natural infection. The results suggest that products of synthetic gene constructs may be a suitable basis for an anti-merozoite vaccine.